2008
DOI: 10.1196/annals.1454.027
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effects of Environmental Exposure to Arsenic and Lead on Children in Region Lagunera, Mexico

Abstract: DNA damage and DNA repair ability by means of the comet assay and the hydrogen peroxide challenge in lymphocytes from 65 children exposed simultaneously to As and Pb in Region Lagunera, Mexico. The first exposure scenario was concerned with natural As contamination in drinking water affecting all children, particularly those attending the schools farthest from (Gomez Palacio) and closest to the smelter (Pedro Garcia). The second scenario related to additional Pb and As soil and dust contamination in the school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 40 publications
(88 reference statements)
0
28
0
Order By: Relevance
“…To our knowledge, no studies in children examined the association between BLL and 8-OH-dG to compare with our findings. However, four studies in children examined the relation between BLL and DNA damage or DNA repair as measured by the comet assay (also known as single cell gel electrophoresis) or other methods (such as micronuclei (MN) and sister chromatid exchange (SCE) levels in peripheral lymphocytes) (Jasso-Piñeda et al, 2012, Mendez et al, 2008, Mielzynska et al, 2006; Yanez et al, 2003) and found higher levels of DNA damage in children with higher BLL compared to children with lower BLL. In addition, Mielzynska and colleagues (2006) observed a direct association between BLL and DNA damage as measured by number of micronuclei per 1000 cells in peripheral lymphocytes in 5–14 year old Polish children with a mean BLL of 7.7 μg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies in children examined the association between BLL and 8-OH-dG to compare with our findings. However, four studies in children examined the relation between BLL and DNA damage or DNA repair as measured by the comet assay (also known as single cell gel electrophoresis) or other methods (such as micronuclei (MN) and sister chromatid exchange (SCE) levels in peripheral lymphocytes) (Jasso-Piñeda et al, 2012, Mendez et al, 2008, Mielzynska et al, 2006; Yanez et al, 2003) and found higher levels of DNA damage in children with higher BLL compared to children with lower BLL. In addition, Mielzynska and colleagues (2006) observed a direct association between BLL and DNA damage as measured by number of micronuclei per 1000 cells in peripheral lymphocytes in 5–14 year old Polish children with a mean BLL of 7.7 μg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage has been detected in ovarian tissue in a dose-dependent manner [29]. Similarly higher extent of DNA fragmentation has also been reported in different communities of San Luis Potosi State [37] and in different schools of Mexico [36] located at different distances from arsenic smelter area.…”
Section: Discussionmentioning
confidence: 67%
“…People of India (Murshidabad) exposed to arsenic contaminated drinking water express greater extent of DNA migration compared to unexposed population [35]. Mendez-Gomez et al [36] and Jasso-Pineda et al [37] studied different arsenic exposed areas in Mexico and observed greater fragmentation of DNA damage in areas located nearest to arsenic source (Table 2).…”
Section: Detail Description Of Findingsmentioning
confidence: 99%
“…This region has historically had high levels of As in drinking water (Del Razo et al 1990;Marnell et al 2003;Méndez-Gómez et al 2008). Arsenic concentrations in water used for drinking and cooking have been reported to fall within the range of 0.01-0.62 mg/l.…”
Section: Study Site and Selection Of Participantsmentioning
confidence: 96%